DETERMINATION OF SUITABLE RECREATIONAL AREAS IN ADANA PROVINCE CUKUROVA DISTRICT BY AHP TECHNIQUE - Kocan, Nurhan; Sengur, Seyma; Alp, Muhibe Asli; Corbaci, Omer Lutfu; Ozkan, Esra Cetinkaya (Vilnius Gediminas Tech Univ, 2025)
Recreation is people's whole activity to regain their lost energy. In urban recreation areas, today's people can escape city life and reach themselves and nature at some point. In this context, the distribution, size, and accessibility of recreation areas in cities gain importance. The research aims to determine potential recreation areas by considering the natural and physical characteristics of the Adana Province Cukurova district. The criteria and importance weights of the criteria related to the natural and physical characteristics of Cukurova district, which is the research area, were determined by Analytic Hierarchy Process (AHP) technique. The data layers of the criteria were overlapped using the Weighted Linear Combination Technique in ArcMap program using the importance weights and a map of potential recreation areas was created. The results show that 2.6% of the region has low, 72.2% has medium, and 25.2% has high recreational potential. The western part of Seyhan Dam Lake has been identified as the most suitable area for recreation. Providing a holistic green space system will enable the development of the city's natural potential. In addition, the areas proposed to be planned as recreational areas will contribute to urban ecosystem services and improve the quality of urban life. To define recreational suitable areas provides effective and quick solutions to manage urban sprawl on ecological. (Referee 1).
Keywords: urbanization; AHP; urban green spaces; recreational suitability; GIS.